(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2014)
أجري البحث على عينة من المعلمين والمعلمات في محافظة اللاذقية بلغ عددهم (688) معلماً ومعلمة, (370) معلمة, (318) معلماً, سحبت العينة وفق قانون ريتشارد جيجر لسحب العينات بدقة (0,05).استخدمت الباحثة مقياس الضغوط النفسية (إعداد الباحثة), ومقياس التوافق المهني (إعداد الباحثة), هدفت الدراسة إلى تعرف العلاقة بين الضغوط النفسية والتوافق المهني لدى أفراد العينة, وتعرف الفروق بين الذكور والإناث على مقياس الضغوط النفسية وكذلك على مقياس التوافق المهني, وتعرف الفروق بين أفراد العينة الذين لديهم خبرة مع الأفراد الذين ليس لديهم خبرة (الخبرة فوق الخمس سنوات) على مقياس الضغوط النفسية وكذلك على مقياس التوافق المهني. توصلت الباحثة إلى النتائج التالية: لا توجد علاقة ارتباط بين الضغوط النفسية والتوافق المهني لدى أفراد العينة. لا توجد فروق على مقياسي الضغوط النفسية و التوافق المهني وفق متغير الجنس. لا توجد فروق بين أفراد العينة على مقياسي الضغوط النفسية والتوافق المهني وفق متغير الخبرة. The study was conducted on a sample of teachers in the province of Latakia numbered (688) teachers, (370) females, (318) males, sample was withdrawn according to the law of Richard Gebre sampling accuracy (5,5) researcher used scale of psychological stress, and vocational adjustment scale.The study aimed to identify the relationship between psychological stress and vocational adjustment to the members of the sample, and to identify the differences between males and females on the scale of psychological stress, as well as on the scale of vocational adjustment and to identify the differences between the sample members who have experience with individuals who do not have experience (experience over five years) on a scale of psychological stress, as well as on the scale of vocational adjustment. Researcher reached the following conclusions. There is no correlation between psychological stress and vocational adjustment members of the sample. There are no differences between males and females on the scale of psychological stress, as well as on the scale of vocational adjustment.